Strategi Branding Dan Pemasaran Yang Efektif Untuk Meningkatkan Penjualan Trfthing Di Era Bisnis Pakaian Nemee Supplay - Tartilah, Nala; Fahriz, Muhammad Dafa; Octoviani, Aniza (Magister Manajemen Universitas Wisnuwardhana, 2024)
Abstract. Millennial clothing needs are increasingly diverse, following changing times. For example, the need for clothing is not explained by the existence of branded and quality goods. With goods that can be reached by all millennial groups. Regarding branding strategies, thrifthing businesses must have a strong and attractive image for consumers. A good brand image can help a business to become better known and liked by consumers. The purpose of qualitative research is to understand the phenomena encountered is research. Including understanding, perception, motivation and action. In a special natural context by utilizing various natural methods such as in depth interviews, observation, or documentation to gain a better understanding of various aspects of human behavior and experience. Data obtained from the list of research questions as a result of research conducted via zoom has been presented. Several findings can be found regarding the data that researchers need.in this research, the owner of Nemee Supply obtained data onhow to determine market segmentation and not follow trends too much, so data from informants is really needed to explain the acquisition of research data which can be used as an interview draft. The conclusion of the research is to follow fashion influencers who have influence on social media. The fashion trends they follow, pay attention to what items are in high demand by customers and what is trending in the shop, build a strong identity which includes choosing a name and logo, which reflects the character and values of the Nemee Supplay business, and provide a good customer experience